Comparison between the effect of single-dose radial extracorporeal shock wave and local corticosteroid injection in treatment of patients with carpal tunnel syndrome - Lamis S Ahmed; Abeer H Ismaiel; Nahed H Taha (Journal of Medicine in Scientific Research, 2021)
Objective To evaluate the efficacy of radial extracorporeal shock wave therapy (rESWT) compared with local corticosteroid injection (LCsI) in reducing pain and improving the function of patients with mild and moderate carpal tunnel syndrome (CTS) over 6 months. Patients and methods We studied 40 patients with mild and moderate CTS, where 20 patients received single-dose rESWT and the second group was treated with LCsI. Both groups had been assessed at baseline and at 1, 3, and 6 months after treatment using Boston self-assessment questionnaire (BQ) and visual analog scale (VAS) and at baseline and after 3 months using neurophysiological studies. Our prospective study compared efficacy in relieving pain and improving clinical function between single-dose rESWT and LCsI over 6 months. We subdivided our patients into mild and moderate groups and comparing improvement in outcome variables after treatment with rESWT and LCsI. Results There was a significantly higher improvement in symptom severity scores, functional scores, and BQ scores and decrease in VAS at 3 and 6 months, with significant improvement in sensory nerve conduction parameters at 3 months in the rESWT group compared with the LCsI group. When compared with the baseline, there was a significant reduction of VAS and functional score, symptom severity scores, BQ scores at third and sixth months, and electrophysiologic parameters at third month in the rESWT group. The LCsI group had no statistically significant improvement in all outcome variables at sixth month. Moreover, there were highly positive significant correlations between peak sensory latency of median nerve and the clinical outcomes (VAS and BQ score) at the sixth month after rESWT and between motor latency of median nerve and BQ score in mild and moderate CTS groups. Conclusion Single-dose rESWT is a noninvasive and convenient method for treating mild and moderate CTS with long-term beneficial effect lasting up to 6 months compared with LCsI.